Los accidentes laborales y la responsabilidad entre las compañías de guardias de seguridad y la entidad contratante - Edith Jadira, Basantes Ilbay (2021)
The Constitution of the Republic of Ecuador guarantees the right to work and recognizes all types of work, under a dependent or autonomous relationship. Within the workplace, it seeks to safeguard the rights of workers to carry out their work in a suitable environment that guarantees their health and personal integrity. Every day workers are exposed to occupational accidents derived from their usual activity such as private security, where their workers expose their lives due to the responsibility of their functions. There are legally constituted surveillance and private security companies that offer their complementary services to state entities and due to the eminent risk in which the security guards are, it is necessary to establish the responsibility that the contracting entities have, as well as the security company in work accidents Constituent Mandate No. 8 establishes that contracting entities may agree to the use of complementary activities such as security for their facilities and a civilian must sign two contracts; and, work that will be with the security company and a work that must be with each of the security guards required in said contract, schedules and remuneration will be established.